Pengaruh Penggunaan Media Pembelajaran Berbasis Vectorian Giotto terhadap Motivasi dan Hasil Belajar Siswa SDIT Di Kabupaten Oku Timur - Nesi Anti Andini; Khusnatul Amaliah; Ariyansyah (Universitas Kanjuruhan Malang, 2021)
Utilization of media learning based on ICT, especially in the eyes of subjects IPA at the level of elementary school can optimize the process of learning the teaching that takes place. This is very relevant when using learning media to convey information. One of the media that can support is Vectorian Giotto. Research objectives This is to explain the effect of using vectoriangiotto based learning media on the motivation and learning outcomes SDIT students in East OKUT. This research is quantitative with a quasi- experimental type. Population and samples were used in the study amounted to 136 students. Data collection techniques: observation, tests, and questionnaires. Data analysis techniques, descriptive statistical techniques and inferential statistical techniques. Descriptive analysis results; The mean scores of motivationand learning outcomes for grade IV were 79.26 and 93.33. results of statistical inferential by using test wilcoxion obtained value Asymp . Sig. (2-tailed) for 0000 is smaller than 0.05, means that there is the influence of the media learning based vectoriangiotto with the results of learning. To see the motivation of students to use the medium of learning obtained a value of 0.000 is smaller than 0.05, which means that there is the influence of the media learning based vectoriangiotto with the motivation to learn.